Indonesian Climatic Factors and Its Effect on Cocoa Productivity - Aura Dhamira; Herdiana Anggrasari (Westscience Press, 2024)
One of the important aspects in cocoa cultivation is productivity, as it is related to the ability of national cocoa producers to meet market demand. Cocoa productivity is affected by many factors, including climate factors. On this basis, this study aims to determine the trend of national cocoa productivity and climatic factors (maximum temperature, minimum temperature, mean temperature, and rainfall) and to determine the influence of climatic factors on cocoa productivity. By applying a descriptive method, this research utilized secondary data with a time span between 1961-2021, which were analyzed using quadratic regression model. From the analysis, it was clear that there had been increasing tendency for national cocoa productivity, maximum temperature, minimum temperature, mean temperature and rainfall from year to year. Meanwhile, the climatic factors that affect cocoa productivity are the maximum temperature, minimum temperature, and mean temperature with an optimum point of 30.53°C; 21.31°C and 25.87°C respectively. Temperature generally has a negative effect on cocoa productivity, although it does not have a big impact. However, continuous exposure to temperature will lead to a more harmful threat to cocoa productivity. This research contributes to the use of non-linear regression analysis, especially quadratic regression model in determining climatic factors that influence cocoa productivity in Indonesia, considering that not many studies have used similar model.